Pembelian Lahan Virtual pada Platform Metaverse Menggunakan Mata Uang Kripto Perspektif Hukum Islam - Ulfita, Rifka Asri (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
Virtual land in the metaverse can be understood as the area being traded to investors. The area is a clone of the original area in the real world. Through this platform, one can virtually have an office, workspace and other functions. In this virtual world, the developer has provided many options and other supporting features. Virtual land purchase transactions are projected to use cryptocurrencies. Therefore, this study answers two paradigms that intersect with one another. On the one hand, virtual land purchases still reap various polemics in Islamic law. On the other hand, the use and investment of cryptocurrencies are also still experiencing various upheavals in the legal implementation. This study concludes that the practice of investing in buying virtual land on the metaverse platform is permissible with the terms and conditions: having sufficient knowledge about virtual investment and having sufficient experience in non-physical businesses in order to survive and generate profits.